Selection of Computer Private College to Use Elimination Methods and Options of Expressing Reality (ELECTRE) - Oka Wantika Zuhairra; Ramalia Noratama Putri (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
Higher education is a continuation of secondary education which is prepared for students to become members of society who have academic and professional abilities who can apply, develop and create science, technology and arts. Higher education contains background problems, problem formulations and research objectives. Choosing a college has many aspects that must be considered, such as the location of the college, tuition fees, distance from residence, accreditation, levels, and choice of computer program majors. The hesitation in choosing a college to major in computer is often an obstacle for every prospective student. Especially with the many universities that exist today, both private and public universities. This makes prospective students often feel unfamiliar, confused, lack of information about tertiary institutions so that they are wrong in making choices. So that the solution from researchers designed information systems that are useful for assisting prospective students in choosing private universities for web-based computer programs, using the ELECTRE mysql database method. The results of research on private universities with the Electre method, it can help and provide recommendations and the best alternative decision solutions to prospective students in making decisions with many criteria.